Peningkatan Literasi Digital Bagi Siswa Paket C PKBM Bina Insan Kamil Melalui Pelatihan Dasar Komputer Dan Internet - Okky Prasetia; Syaeful Machfud; Gigih Amrillah Ibnurhus (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Digital literacy is currently highly needed by society, especially in the field of education. Modern developments demand that people be able to operate digital information and communication technology, so the public's knowledge must be able to keep pace. PKBM Bina Insan Kamil is a non-formal educational institution operating in South Tangerang City. One of its non-formal education programs is equivalency education, which provides general education equivalent to elementary school (SD/MI), junior high school (SMP/MTs), and senior high school (SMA/MA), including Package A, Package B, and Package C programs. The goal of equivalency education is to provide opportunities for disadvantaged communities (such as those who have never attended school or dropped out due to lack of opportunities) to recover and continue their education. To improve the digital literacy competency of learners, especially Package C students, careful treatment and mentoring are required to properly prepare them for the era of the Industrial Revolution 5.0 and Society 5.0. The implementation method is carried out in three stages: planning, implementation, and evaluation, using a social approach, which takes place over a one-day period. The results of the activity indicate that this training is effective in improving the digital literacy of Package C students at PKBM Bina Insan Kamil. This activity is also expected to empower Package C students to be more adaptable to technology, improve their quality of life, and support student development through the use of digitalization.